Implementasi Ekoliterasi Melalui Pembelajaran Berbasis Proyek Pada Pendidikan Anak Usia Dini - Sari, Muntia; Effendie, Rustam; Sakerani, Sakerani (JEA (Jurnal Edukasi AUD), 2025)
Environmental issues and education are critical components in promoting sustainability, particularly in early childhood education. Despite the growing recognition of eco-literacy's importance, there remains limited research on project-based learning models that emphasize experiential approaches to address local environmental challenges faced by young children. This study aims to explore the implementation of eco-literacy through project-based learning at TK Alam Berbasis Karakter Sayang Ibu Kota Banjarmasin. Using a qualitative case study design, data was collected through observations, interviews, and document analysis. Data analysis was conducted using techniques of data reduction, data display, and conclusion drawing, with triangulation employed to ensure data validity. The findings reveal that eco-literacy was effectively implemented through two main project-based learning activities: the ecobrick and eco enzyme projects. The projects were conducted over eight sessions, divided into three phases: initiation, development, and conclusion. At the end of the learning process, the teacher facilitated a reflection activity by encouraging children to express their feelings through free drawing. This reflective process allowed children to articulate their thoughts and emotions regarding waste and environmental care, reinforcing the learning process. The study emphasizes the importance of integrating eco-literacy in early childhood education and highlights the value of context-specific, experiential learning models in fostering environmental awareness and responsibility among young learners.